2022
DOI: 10.1161/circimaging.121.013762
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Cardiovascular Health Is Associated With Lower Prevalence, Incidence, Extent, and Progression of Extracoronary Calcification: MESA

Abstract: Background: Ideal cardiovascular health (CVH) is associated with a lower incidence of cardiovascular disease. Extracoronary calcification (ECC)—measured at the aortic valve, mitral annulus, ascending thoracic aorta, and descending thoracic aorta—is an indicator of systemic atherosclerosis. This study examined whether favorable CVH was associated with a lower risk of ECC. Methods: We analyzed data from MESA (Multi-Ethnic Study of Atherosclerosis) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Arterial medial calcification increases arterial stiffness, blood pressure and heart workload, impairs vascular compliance and vascular reactivity. Arterial medial calcification is an independent risk factor for development of stroke, cardiovascular diseases and mortality in type 2 diabetes mellitus ( 4 , 28 ). Current anti-calcifying therapies may delay but can not effectively reduce existing arterial calcification and conduit vessel compliance ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial medial calcification increases arterial stiffness, blood pressure and heart workload, impairs vascular compliance and vascular reactivity. Arterial medial calcification is an independent risk factor for development of stroke, cardiovascular diseases and mortality in type 2 diabetes mellitus ( 4 , 28 ). Current anti-calcifying therapies may delay but can not effectively reduce existing arterial calcification and conduit vessel compliance ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…A US‐based multiethnic cohort revealed that higher Life's Simple 7 levels were associated with 57%, 56%, 70%, and 54% lower risk of incident aortic valve calcification, mitral annulus calcification, ascending thoracic aorta calcification, and descending thoracic aorta calcification, respectively. 38 However, as a predecessor to LE8, Life's Simple 7 has certain limitations. For instance, Life's Simple 7 is less sensitive to individual variations and cannot be used to assess dose–response effects.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Circulation: Cardiovascular Imaging , Ogunmoroti et al 2 add to the literature by evaluating the association of cardiovascular health (CVH) with the overall burden and progression of ECC. The authors stratified participants of MESA (Multi-Ethnic Study of Atherosclerosis), a population-based cohort study of 6814 adults without known CVD, based on their CVH score.…”
mentioning
confidence: 99%
“…3 Numerous prior studies have consistently shown that the CVH score is associated with meaningful clinical outcomes—adults with more favorable CVH scores have a significantly lower burden of subclinical disease and experience fewer incident cardiovascular events than adults with poor scores. 4–7 Ogunmoroti et al 2 determined whether MESA participants with more favorable CVH also had a lower burden of ECC at baseline and slower progression over a mean of 2.4 years follow-up. ECC sites were mitral annular calcification, aortic valve calcification (AVC), ascending thoracic aorta (ATAC), and descending thoracic aorta (DTAC).…”
mentioning
confidence: 99%